Captive Markets - Plunkett, Leah A. (2013)
Today, inmates in county jails nationwide are billed for some or all of the costs of their room-and-board behind bars. Statutes authorizing counties to implement these “pay-to-stay” programs are on the books in roughly 70% of states, yet the financial mechanism on which these programs typically rely is not well understood. Although the pay-to-stay obligation bears some resemblance to familiar citizen-state financial transactions — such as fines and penalties, restitution, taxes, and fees — it in fact usually belongs to a distinct model that this Article calls the “government-imposed-loan.” This Article provides an overview of the landscape of pay-to-stay programs followed by an articulation of the imposed-loan model. It then offers an initial assessment of the normative desirability of the imposed-loan model, focusing on pay-to-stay programs but considering other limited areas in which versions of the model exist or could develop. The imposed-loan structure raises concerns in two primary areas: citizen privacy and governmental services. This model is likely to require that citizen-borrowers disclose personal financial information — some of it with a dubious substantive link to the underlying issue for which a given service was provided — to the government on a long-term basis. It is also likely to create some disincentive for these borrowers to work, thus increasing the likelihood that they will consume governmental services in addition to the one for which the loan was imposed. On balance, it does not appear that the familiar structure of a consumer loan translates well for use in captive markets, such as jail housing or emergency services, where citizens essentially have no choice but to consume services provided by the government through its police powers. However, in light of the current fiscal constraints faced by local and state governments, imposed-loans are likely to keep proliferating